2016
DOI: 10.1111/ans.13464
|View full text |Cite
|
Sign up to set email alerts
|

Enterobius vermicularis and its role in paediatric appendicitis: protection or predisposition?

Abstract: E . vermicularis was found to be more common in females and those of European descent. Seventy-seven percent of patients with E . vermicularis did not have concurrent acute inflammation of the appendix on histological examination. The question remains as to whether infestation is protective of inflammation or whether infestation causes appendiceal colic and subsequent appendicectomy of a non-inflamed appendix, thereby protective of the morbidity of acute appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 12 publications
6
28
0
1
Order By: Relevance
“…Our case had no eosinophilia. It has also been observed that EV is more commonly found in appendices removed from females and children of European descent . These factors were present in our patient (Table ).…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Our case had no eosinophilia. It has also been observed that EV is more commonly found in appendices removed from females and children of European descent . These factors were present in our patient (Table ).…”
Section: Discussionsupporting
confidence: 73%
“…EV is commonly found on appendicectomy. In developed countries, EV has been confirmed histologically in 1.2–7.1% of appendicectomy specimens . For many years, it has been assumed that EV leads to appendicitis by blocking the lumen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations